2015
DOI: 10.1093/mnras/stu2510
|View full text |Cite
|
Sign up to set email alerts
|

Witnessing the transformation of a quasar host galaxy at z = 1.6

Abstract: A significant minority of high redshift radio galaxy (HzRG) candidates show extremely red broad band colours and remain undetected in emission lines after optical 'discovery' spectroscopy. In this paper we present deep GTC optical imaging and spectroscopy of one such radio galaxy, 5C 7.245, with the aim of better understanding the nature of these enigmatic objects. Our g-band image shows no significant emission coincident with the stellar emission of the host galaxy, but does reveal faint emission offset by ∼3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…For 5C 7.245, we also show the g-band photometry of the extended blob of emission located ∼1 SW of the near-infrared position of the radio galaxy (blue). Humphrey et al (2015) argued that we here witness a rare (or rarely observed) phase in the evolution of quasar hosts, when stellar mass assembly, accretion onto the back hole, and/or powerful feedback activity have eradicated cold gas from the central ∼20 kpc, but is still in the process of cleansing cold gas from its extended halo.…”
Section: Resultsmentioning
confidence: 72%
See 4 more Smart Citations
“…For 5C 7.245, we also show the g-band photometry of the extended blob of emission located ∼1 SW of the near-infrared position of the radio galaxy (blue). Humphrey et al (2015) argued that we here witness a rare (or rarely observed) phase in the evolution of quasar hosts, when stellar mass assembly, accretion onto the back hole, and/or powerful feedback activity have eradicated cold gas from the central ∼20 kpc, but is still in the process of cleansing cold gas from its extended halo.…”
Section: Resultsmentioning
confidence: 72%
“…2). Long-slit spectroscopy presented by Humphrey et al (2015) detected no lines from the K-band position at a 3σ limit of ∼3 × 10 −17 erg s −1 cm −2 . However, these authors detected HeII λ1640, CII] λ2326, [NeIV] λ2423 and MgII λ2800 at the position of the g-band blob to the south-east at a redshift of z = 1.609, consistent with the tentative detection of Hα at z = 1.61 reported by W01.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations